Comparison of Dental Students' Self‐Evaluation and Faculty Evaluation of Communication Skills During a Standardized Patient Exercise. Issue 10 (1st October 2018) - Wiener, R. Constance; Waters, Christopher; Doris, Joan; McNeil, Daniel W.
Abstract : The aims of this retrospective study, conducted in 2017, were to explore dental students' perceptions of their first standardized patient encounters and to assess the relationship between students' self‐evaluation and faculty members' evaluation of students' communication skills in those encounters. Data from a simulation training laboratory at one U.S. dental school were obtained for all 46 second‐year students, who had a standardized patient communication learning session. The students had completed self‐evaluations before and after a debriefing with a clinical psychology and/or social work faculty member and three or four student peers. The faculty members had also completed evaluations of the students' communications skills. The results showed that the students found the standardized patient encounter helpful. The students rated "making an introduction" most positively. Students had a weighted Kappa agreement of 0.22 (p=0.024) with the faculty evaluations on their post‐debriefing evaluation of overall communication skills, which was within the 0.21–0.40 range of fair agreement. This study found that, during their first standardized patient simulation exercise, the second‐year students rated their overall communication skills in fair agreement with the faculty member after debriefing.